Near-net-shape production of hollow titanium alloy components via electrochemical reduction of metal oxide precursors in molten salts - Hu, Di; Xiao, Wei; Chen, George Zheng (Springer, 2013)
Metal oxide precursors (ca. 90 wt pct Ti, 6 wt pct Al, and 4 wt pct V) were prepared with a hollow structure in various shapes such as a sphere, miniature golf club head, and cup using a one-step solid slip-casting process. The precursors were then electro-deoxidized in molten calcium chloride [3.2 V, 1173 K (900 C)] against a graphite anode. After 24 hours of electrolysis, the near-net-shape Ti-6Al-4V product maintained its original shape with controlled shrinkage. Oxygen contents in the Ti-6Al-4V components were typically below 2000 ppm. The maximum compressive stress and modulus of electrolytic products obtained in this work were approximately 243 MPa and 14 GPa, respectively, matching with the requirement for medical implants. Further research directions are discussed for mechanical improvement of the products via densification during or after electrolysis. This simple, fast, and energy-efficient near-net-shape manufacturing method could allow titanium alloy components with desired geometries to be prepared directly from a mixture of metal oxides, promising an innovative technology for the low-cost production of titanium alloy components.